Detección de introgresión genética en la perdiz roja (Alectoris Rufa), mediante análisis del ADN mitocondrial - Ramiro García, Javier; Sevane Fernández, Natalia; Tupac-yupanqui Segastegui, Isabel (Revista Complutense de Ciencias Veterinarias, 2007)
The analysis of D-Loop, the source of mtDNA replication, in populations from different species of partridges, has proved the existence of differential haplotypes for the Red, Greek and Chuckar partridges. Based on this, we have used a technique using the mitochondrial D-Loop amplification and sequencing which allows the detection of specific mutations, so that inter-specific crossings in the maternal line can be traced. A total of 1410 partridges divided into 282 groups of 5 individuals have been analysed. Results show that in 87 of these groups, there is genetic introgression of partridge species different from the red in at least one individual.